Deep Vein Thrombosis, Raynaud's Phenomenon, and Prinzmetal Angina in a Patient with Glanzmann Thrombasthenia - Nurden, Alan; Mercié, Patrick; Zely, Pascal; Nurden, Paquita (Case Reports in Hematology, 2012)
Patients with Glanzmann thrombasthenia fail to form large platelet thrombi due to mutations that affect the biosynthesis and/or function of the αIIbβ3 integrin. The result is a moderate to severe bleeding syndrome. We now report unusual vascular behaviour in a 55-year-old woman with classic type I disease (with no platelet αIIbβ3 expression) and a homozygous ITGA2B missense mutation (E324K) affecting the terminal β-propeller domain of αIIb. While exhibiting classic bleeding symptoms as a child, in later life this woman first developed deep vein thrombosis after a long air flight then showed vascular problems characteristic of Raynaud’s phenomenon, and finally this year she presented with chest pains suggestive of coronary heart disease. Yet while coronary angiography first showed a stenosis, this was not seen on a second examination when she was diagnosed with coronary spastic angina and Prinzmetal phenomenon. It is significant that the absence of platelet aggregation with physiologic agonists had not prevented any of the above cardiovascular or vascular diseases.